Write it right: A handbook for students - Peck, John; Coyle, Martin (New York Palgrave Macmillan, 2005)
Feedback from users of the Student's Guide to Writing suggested that some students find it hard to make time to read a book from cover to cover, and need a quick, problem-solving approach to improving their writing. This is what is offered in Peck and Coyle's new book Write it Right. Write it Right offers advice in short 'modules' which target particular tasks (such as applications or essays) or common problems (like punctuation). It will be ideal for students who are short of time, but nevertheless want to improve their writing.